Association of Mineralocorticoid Receptor Antagonists With the Mortality and Cardiovascular Effects in Dialysis Patients: A Meta-analysis - Gou, Wen-Jun; Zhou, Fa-Wei; Providencia, Rui; Wang, Bo; Zhang, Heng; Hu, Shou-Liang; Gao, Xiao-Li; Tuo, Yan-hong; Zhang, Yong; Li, Tian (Frontiers in Pharmacology, 2022)
Whether Mineralocorticoid receptor antagonists (MRA) reduce mortality and cardiovascular effects of dialysis patients remains unclear. A meta-analysis was designed to investigate whether MRA reduce mortality and cardiovascular effects of dialysis patients, with a registration in INPLASY (INPLASY2020120143). The meta-analysis revealed that MRA significantly reduced all-cause mortality (ACM) and cardiovascular mortality (CVM). Patients receiving MRA presented improved left ventricular mass index (LVMI) and left ventricular ejection fraction (LVEF), decreased systolic blood pressure (SBP) and diastolic blood pressure (DBP). There was no significant difference in the serum potassium level between the MRA group and the placebo group. MRA vs. control exerts definite survival and cardiovascular benefits in dialysis patients, including reducing all-cause mortality and cardiovascular mortality, LVMI, and arterial blood pressure, and improving LVEF. In terms of safety, MRA did not increase serum potassium levels for dialysis patients with safety. Systematic Review Registration: (https://inplasy.com/inplasy-protocol-1239-2/), identifier (INPLASY2020120143).